Persistence of SARS-CoV-2 Infection in Severely Immunocompromised Patients With Complete Remission B-Cell Lymphoma and Anti-CD20 Monoclonal Antibody Therapy: A Case Report of Two Cases - Martínez-Chinchilla, Carlos; Vazquez-Montero, Lucía; Palazón-Carrión, Natalia; Fernández-Román, Isabel M.; López-Barba, José; de la Cruz-Merino, Luis; Rodríguez-Baño, Jesús; Palacios-Baena, Zaira R. (Frontiers in Immunology, 2022)
Immunosuppressant conditions such as hematological malignancies increase the risk of severe SARS-CoV-2 infection. It has been described in the literature that patients on anti-CD20 maintenance therapies for lymphoid malignancies are susceptible of having recurrent flares together with viral replication or re-infections, although these cases are scarce. These patients are not well represented in randomized controlled trials and as a consequence, the evidence for the use of certain treatments in this scenario is lacking. We present two cases of patients with B-cell lymphoma on remission and treated with rituximab on maintenance. They developed at least 1 flare of COVID-19 after acute infection and always after receiving rituximab. RT-PCR was positive in nasopharyngeal swab and also in plasma. Patients were treated during flares with remdesivir, hyperimmune plasma and corticosteroids. These two cases showed the unresolved problem of COVID-19 in immunosuppressant patients and showed that despite the vast amount of information available on SARS-CoV-2, information in this subgroup of patients is lacking.